Encapsulation Effect on Performance and Stability of Organic Solar Cells. Issue 15 (8th June 2020) - Planes, Emilie; Juillard, Sacha; Matheron, Muriel; Charvin, Nicolas; Cros, Stéphane; Qian, Deping; Zhang, Fengling; Berson, Solenn; Flandin, Lionel
Abstract: To increase the lifetime of organic photovoltaic (OPV) devices and pass European lifetime standards, some encapsulation systems are often used to limit the exposition to oxygen and humidity of solar cells. Despite this progress, the damages induced by the encapsulation process are scarcely studied in literature. In this article, the consequences of the common roll‐to‐roll and vacuum lamination approaches are investigated and compared. The losses of performances are first followed induced by both the encapsulation itself and in a damp heat ageing. The vacuum lamination seems harmless for the solar cells. However, a significant damage is evidenced, even with a relatively mild roll‐to‐roll encapsulation. The degradation mechanisms are further investigated by complementary imaging characterization tools: photoluminescence/electroluminescence imaging and spectroscopy, laser‐beam‐induced current mapping, and correlated to J ( V ) curves. The recent advancements in the optoelectronic domain may allow linking cell performance to localized flaws. It appears that, although the processing conditions are rather homogeneous, the resulting degradation ends up with a strong localization feature. Abstract : Impact of encapsulation on performance and stability of organic solar cell is studied. Delaminations produced during R2R process induce an important performance loss and a weak stability in temperature or/and humidity.